The state of mental well-being among medical students: A review - Prajapati, Raj (Journal of Karnali Academy of Health Sciences, 2025)
Mental well-being constitutes a fundamental aspect of overall wellness, essential for sustaining life and achieving personal goals. In contemporary times, it has become a primary global concern, mainly affecting medical students by raising mental health issues, a problem often ignored by medical colleges and society. Students frequently refrain from discussing this issue due to stigma and professional considerations. This poses a significant challenge for medical colleges striving to develop skilled physicians. Several studies show a notable rise in mental health issues among medical students, negatively impacting their well-being. Key factors include academic stress, personal struggles, institutional problems, social media effects, and loneliness. Poor mental health in these students often results in stress, anxiety, and depression, which are critical mental health concerns. It is therefore recommended that academic workloads be reduced and various mindfulness programs be implemented to address this serious issue.